2020
DOI: 10.3390/ijerph17165833
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Changes in High-Level Aerobic Male Athletes during a Sports Season

Abstract: The aim of this study was to determine the possible changes in plasma of several hormones such as Luteinizing Hormone, Testosterone, Cortisol and Insulin in endurance runners during the sports season. Twenty-one high-level male endurance runners (22 ± 3.2 years, 1.77 ± 0.05 m) participated in the study. Basal plasma hormones were measured at four moments during the season (initial, 3, 6 and 9 months), and were analyzed using ELISA (enzyme-linked immunosorbent assay). Testosterone and Luteinizing Hormone (LH) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Research has reported on the relationship between energy intake and the synthesis of anabolic hormones [ 20 , 21 ]. High-level endurance runners in training periods with an intake below 45 calories per day per kg of fat-free mass (FFM) had decreases in LH and T hormones [ 22 ]. As mentioned above, significant interactions have been observed between TM concentrations and the endocrine system.…”
Section: Introductionmentioning
confidence: 99%
“…Research has reported on the relationship between energy intake and the synthesis of anabolic hormones [ 20 , 21 ]. High-level endurance runners in training periods with an intake below 45 calories per day per kg of fat-free mass (FFM) had decreases in LH and T hormones [ 22 ]. As mentioned above, significant interactions have been observed between TM concentrations and the endocrine system.…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid deficiency generally leads to an energy preservation state, in which energy normally reserved for growth and reproduction is reduced and diverted to more vital functions 117 . As such, athletes in LEA states have reduced thyroid hormone levels 25,68,77,115,118 . These deficiencies result in decreased growth and reproductive function, which is evident when considering the amenorrheic athlete 119 .…”
Section: Performance and Health Impairments Of Lea And Red-smentioning
confidence: 99%
“…Insulin is also an anabolic hormone: it activates glucose uptake, glycogen synthesis, protein synthesis, and inhibits protein degradation 25,116,120,121 . Circulating glucose is the primary source of energy in the body; blood glucose is tightly regulated by insulin and its counteracting hormone, glucagon.…”
Section: Hormonal and Metabolic Functionmentioning
confidence: 99%
See 2 more Smart Citations